Sosialisasi Penggunaan Gadget Terhadap Penanaman Nilai – nilai Moral pada Anak TPQ Masjid Nurul Ihsan Padang - Indra, Novalia; Zurwanty, Recy Harviani; Rahmawati, Elmi (CV. ITTC INDONESIA, 2024)
Community Service (PKM) is one form of the Tridharma of Higher Education. This PKM is proposed to carry out socialization and educational activities in one of the mosques in the city of Padang with the theme: Socialization of the Use of Gadgets to instill moral values in TPQ children at the Nurul Ihsan Mosque, Padang, West Sumatra. This activity is proposed to socialize the impact of using gadgets on instilling values and morals in children in Padang. Therefore, we focus on carrying out this activity so that children in Padang can control themselves over the large influence of technology on children's morals today, especially we can see children in the city of Padang. so that children in the city of Padang can know the many influences of using gadgets today. If we cannot control ourselves in using technology nowadays, it can lead to a lack of instilling values and morals in today's children. So many children today do not have good values and morals in everyday life. After implementing the PKM that we carried out for the TPQ children of the Nurul Ihsan Mosque in Padang, which you led, hopefully it can become knowledge and a lesson for the TPQ children of the Nurul Ihsan Mosque in Padang.